Comparação do perfil de metabólitos secundários de cultivares de soja - Arroyo, Victoria Patricia Pena (2021)
Soybean (Glycine max) is one of the most important crops in the world socioeconomic scenario, especially in Brazil. However, this crop is constantly attacked by different pests. Plant resistance against herbivores occurs partially through the production of secondary metabolites such as flavonoids. Wild soybeans and cultivated varieties exhibit different levels of resistance to agricultural pests, which may be a consequence of the variability in their secondary metabolite profiles. Thus, identifying these substances among different genotypes and understanding their role in the insect-plant interaction mechanisms is important for a more comprehensive and reliable characterization of soybean resistance. This work proposes to compare the profile of secondary metabolites between 4 cultivated soybean varieties resistant (PI 229358 and IAC 100) and susceptible (BRS 257 and IAC PL-1) to pests and a wild soybean variety (PI 407270). The chemical profile of young and old leaves in the V3 development stage was analyzed. Plants were grown in a greenhouse and different samples were extracted and analyzed by LC-MS. The analysis of the flavonoid profile in the 5 varieties allowed the identification of 18 isoflavone conjugates (daidzein, genistein and glycitein), some of which were present in greater abundance in old leaves. 39 flavonols were also detected, including kaempferol and quercetin conjugates; accumulated mostly in young leaves. Furthermore, it was shown that wild soybeans have higher levels of flavonoids in their younger leaves, in contrast to cultivated varieties. This information will allow us to understand the dynamics of flavonoids in the insect-plant interaction mechanisms and contribute to the creation of resistant varieties and new targets for the management of agricultural pests, contributing to the sustainable development of agriculture.